The Concept Value of Islamic Education in Magah Duit Culture on the Merriage Process on Dayak Tribe Marriage Process at Central Kalimantan - Syaipullah; Heni Rianti; Muslimah (STIT Al-Quraniyah Manna, 2021)
The aim of this research was to know how the process The Concept Value of Islamic Education in Duit Magah Culture on the Merriage Process of Dayak on the Dayak Tribe Marriage Process in Central Kalimantan. This research used an ethnographic approach. In collecting data the researchers used observation, interview and documentation. The result show that the magah duit for marriage is a community tradition for someone who is getting married. This tradition is not certain in Islamic law, this is because this gift is different from dowry and mut'ah in marriage. As it is implemented in the field, the majority of people use this marriage money apprenticeship as afee walimatul Ursy (wedding party). This giving is not just in form money but also in the form of jewelry and other accessories. The amount of money apprenticeship this marriageis determined by consensus, but it is still the woman who determines it with a relatively high amount, so the men feel that this tradition is very burdensome. Keywords: Islamic Education Value, Maga Duit Culture, Dayak Tribe Marriage